Artemisia of Caria - Bridges, Shirin Yim (Bridges, Shirin Yim. Thinking girl's treasury of real princesses., 2010)
Presents information about the life of the fifth-century B.C.E Greek princess who grew up to be a queen and famous admiral. She is mainly noted for her role as a Persian ally in the Battle of Salamis, in spite of living in a society that placed very little value in women.